SUMUR RESAPAN PADA KOMPLEK PERGUDANGAN SEBAGAI SALAH SATU WUJUD SISTEM DRAINASE BERKELANJUTAN - Amalia, Maya; Hidayati, Aulia (Lambung Mangkurat University Press, 2020)
Increasing number of warehousing areas in South Kalimantan Province is a positive impact in terms of regional economic development. However, the development of the warehousing area also has an environmental impact in the form of changes in land use showed by an increase in the area of warehousing areas which will result in an increase in the volume of surface runoff. As an effort to handle excess surface water due to warehousing activities is to use infiltration wells as a means of sustainable drainage. An area of 5.8 hectares located in the Bati-Bati sub-district, Tanah Laut district is the location where this research was conducted. The method used is a hydrological analysis of the rain and discharge that becomes surface run off and inundation in the area. The 5-year return period was chosen to provide recommendations for the dimensions of the infiltration wells that were applied. The results of the hydrological analysis of the 5-year return period are 53.9 mm/day. Design of wells is 1 m of width and 4 m of depth. The number of infiltration wells is 107 pieces.